Internet Addiction and Styles of Coping with Stress During the COVID-19 Pandemic in Turkey - Gezgin Yazıcı, Havva; Utaş Akhan, Latife (Addicta: The Turkish Journal on Addictions, 2022)
This study was conducted in descriptive and cross-sectional design to identify the status of internet addiction among university students and their styles of coping with stress during the coronavirus disease 2019 pandemic in Turkey. The study population was the total of all students (N = 750) enrolled at two universities in Turkey. The whole of the study universe was targeted, but the research was ultimately conducted with the 568 students who agreed to participate. The study data were collected with a Personal Data Form, the Young Internet Addiction Test-Short Form, and the Styles of Coping with Stress Scale. It was found that most of the students spent 3–5 hours on the internet during the weekdays and on the weekends; 83.9% connected to the internet via their cellphones, and a large majority (82.6%) used the internet for logging into social media. Among the ways the students coped with stress, the most common was by adopting a self-confident style and a “seeking social support” approach. It was seen that during the coronavirus disease 2019 pandemic, the students were moderately addicted to the internet and that among the most common styles they adopted to cope with stress was by adopting a self-confident style and seeking social support approach.